Ultrahigh high-strain-rate superplasticity in a nanostructured high-entropy alloy - Nguyen, Nhung Thi-Cam (Nat Commun, 2020)
Superplasticity describes a material’s ability to sustain large plastic deformation in the form of a tensile elongation to over 400% of its original length, but is generally observed only at a low strain rate (~10(−4) s(−1)), which results in long processing times that are economically undesirable for mass production. Superplasticity at high strain rates in excess of 10(−2) s(−1), required for viable industry-scale application, has usually only been achieved in low-strength aluminium and magnesium alloys. Here, we present a superplastic elongation to 2000% of the original length at a high strain rate of 5 × 10(−2) s(−1) in an Al(9)(CoCrFeMnNi)(91) (at%) high-entropy alloy nanostructured using high-pressure torsion. The high-pressure torsion induced grain refinement in the multi-phase alloy combined with limited grain growth during hot plastic deformation enables high strain rate superplasticity through grain boundary sliding accommodated by dislocation activity.